1999
DOI: 10.1023/a:1026621207664
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Noninvasive tests for Helicobacter pylori are increasingly used. Recently, an enzyme immunoassay for H. pylori detection in feces has been put on the market. Aim of this multicenter study was to evaluate the usefulness of this novel test as a predictor of H. pylori status in the pretreatment setting. Three hundred consecutive patients were enrolled. None of the patients had received any eradicating treatment in the last 12 months, and all underwent gastroscopy with biopsies of the antrum and body for histology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The H. pylori stool test is also favorable in young children in whom serology and breath tests may be unreliable or difficult to perform. The superior sensitivity and specificity has been confirmed by many studies which found a pretreatment sensitivity and specificity of 63–100% [17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27]. In a recently published meta-analysis by Gisbert and Pajares [27], 4,769 untreated patients from 43 studies were examined.…”
Section: Hpsa Testmentioning
confidence: 97%
“…The H. pylori stool test is also favorable in young children in whom serology and breath tests may be unreliable or difficult to perform. The superior sensitivity and specificity has been confirmed by many studies which found a pretreatment sensitivity and specificity of 63–100% [17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27]. In a recently published meta-analysis by Gisbert and Pajares [27], 4,769 untreated patients from 43 studies were examined.…”
Section: Hpsa Testmentioning
confidence: 97%